Selective separation of structure-related alkaloids in Rhizoma coptidis with “click” binaphthyl stationary phase and their structural elucidation with liquid chromatography-mass spectrometry - Liu, Qiaoxia; Qiu, Shiyi; Yu, Hui; Ke, Yanxiong; Jin, Yu; Liang, Xinmiao (Analyst (London), 2011)
It is a new task to separate structure-related compounds into a fraction according to their structural characteristics in a complex traditional Chinese medicine (TCM). This method makes separation of the components of the sample simple and structural elucidation easy. In this study, selective separation of alkaloids in Rhizoma coptidis was realized on a "click" binaphthyl column possessing a planar conjugate structure. Three kinds of alkaloids, aporphine, tetrahydroprotoberberine and protoberberine in Rhizoma coptidis showed better retention than other compounds by virtue of π-π interactions with the stationary phase. Moreover, the "click" binaphthyl column could distinguish the aporphine and tetrahydroprotoberberine alkaloids possessing two benzene rings from the protoberberine alkaloids possessing three benzene rings. After separating on the "click" binaphthyl column, the fractions containing the alkaloids were collected and then analyzed with liquid chromatography-mass spectrometry (LC-MS). Totally, 23 alkaloids were identified, and among these alkaloids, three tetrahydroprotoberberine, two aporphine and seven protoberberine alkaloids were first found in Rhizoma coptidis. These newly found alkaloids are minor compounds, and they are always neglected without eliminating the interference of compounds in large amounts by pre-separation on the "click" binaphthyl column. The typical fragmentation pathways of each class of alkaloids were summarized to illustrate their structures. In the MS(2) spectrum, the loss of a molecule of dimethylamine ((CH(3))(2)NH) was observed as the characteristic loss of aporphine alkaloids. All the tetrahydroprotoberberine alkaloids would undergo the Retro-Diels-Alder (RDA) fragmentation reaction in the MS(2) fragmentation. For protoberberine alkaloids, different characteristic fragmentations were observed with different skeleton structures.